Bioactive Constituents Obtained from the Seeds of Lepidium apetalum Willd - Wang, Sijian (Molecules, 2017)
Three new compounds, apetalumosides C(1) (1), D (2), and 1-thio-β-d-glucopyranosyl(1→1)-1-thio-α-d-glucopyranoside (3), together with twenty-two known ones (4–25) were obtained from the seeds of Lepidium apetalum Willd. Among the known isolates, 5–8, 10–13, 16–20, and 25 were obtained from the genus for the first time; 4, 14, 15, and 21–24 were isolated from the species for the first time. Meanwhile, the NMR data of 16 was first reported here. Their structures were determined by means of chemical and spectroscopic methods. On the other hand, their inhibitory effects on sodium oleate-induced triglyceride (TG) overloading in HepG2 cells were evaluated. As a result, two new compounds (1 and 2), together with known isolates 7–11, 13, 14, 16–18, 20, 21, and 25 possessed significant inhibitory effects in the cells.